Non-intubated Thoracoscopic Surgery—Pros and Cons - Janík, Miroslav; Juhos, Peter; Lučenič, Martin; Tarabová, Katarína (Frontiers in Surgery, 2021)
Pulmonary resection by VATS with single-lung ventilation has become a standardized modality.In 2004, Pompeo reported the resection of pulmonary modules by conventional VATS under intravenous anesthesia without endotracheal intubation.. Avoiding tracheal intubation under general anesthesia can reduce the incidence of complications such as intubation-related airway trauma, residual neuromuscular blockade, ventilation-induced lung injury, impaired cardiac performance, and postoperative nausea. Numerous studies can be found, focusing on comparison of intubated and non-intubated procedures showing that non-intubated VATS reduce the rate of postoperative complications, shorten hospital stay and decrease the perioperative mortality rate. It is obvious that there are no significant differences between intubated and nonintubated surgery in terms of the standard procedures. All the differences between the intubated and non-intubated operation procedure are found in perioperative management of the patient. Moreover, studies on non-intubated thoracic surgery point to shortened hospitalisation, faster recovery etc. But there are also studies on intubated uniportal VATS procedures in combination with ERAS protocol showing shortened hospitalisation and better outcome for patients. Currently, especially with the use of optical intubation canylas, totally intravenous anesthesia (TIVA), BIS and relaxometer, anesthesia is safe for avoiding airway injury, hypercapnia, and there is minimal risk of residual curarization as well as one of the postoperative lung complications such as microaspiration and atelectasis. The patient recovers rapidly from anesthesia and can be verticalised and mobilised soon. It is desirable to take into consideration what type of patient and what lung disease is suitable for non-intubated technique and what is more convenient for intubation.